Analysis of Wind Effects on Tall Buildings: Wind Engineering and Design Considerations - Santosh Kumar, Gottapu (International Journal of Psychosocial Rehabilitation, 2020)
This research paper delves into the critical analysis of wind effects on tall buildings, emphasizing key considerations in wind engineering and design. As the global landscape witnesses an increasing trend in the construction of towering structures, understanding and mitigating the impact of wind on these buildings becomes paramount. The paper begins with an exploration of the historical evolution of wind engineering, laying the foundation for comprehending the complexities involved. Fundamental concepts in wind engineering are elucidated, including wind load calculations and the various factors influencing wind loads on tall structures. The design considerations section focuses on the intricate process of designing tall buildings with a specific emphasis on wind effects, covering aerodynamics, wind tunnel testing, and computational methodologies. Through in-depth case studies, the paper assesses the real-world responses of specific tall buildings to wind loads, offering valuable insights and comparisons between different design approaches. The discussion extends to innovative technologies and materials employed to enhance wind resistance, as well as an exploration of current challenges and future trends in the field. Regulatory standards and codes governing wind loading on structures are scrutinized, evaluating their efficacy. The paper concludes by summarizing key findings, highlighting implications for tall building design, and suggesting avenues for future research. This comprehensive analysis contributes to the broader understanding of wind engineering in the context of tall buildings and informs advancements in design practices and regulatory frameworks.